Implementation Of Agreements In Multi Level Marketing (Mlm) Business Schemes Based On Sharia Principles - Nurjaman, Muhamad Izazi; Rojikin, Ikin; Pary, Hulaiva; Hasim, Syarif; Ayu, Dena (ITB AAS INDONESIA Surakarta, 2023)
Scholars have different opinions regarding MLM business schemes, some forbid and some for conditional permissibility. As for the juhur of contemporary scholars, many of them forbid it. However, the DSN-MUI through Fatwa Number 75 of 2009 allows MLM business schemes on condition that the implementation of a contract is in accordance with sharia principles. Therefore, this study will analyze the implementation of the contract in the MLM business scheme. This research includes sharia economic law research using a descriptive method of literature with a normative juridical approach using secondary data in the form of DSN-MUI Fatwas. This type of research is qualitative research with data analysis techniques, namely data reduction, data presentation and conclusions. The results of this study reveal that based on the substance of the DSN-MUI Fatwa Number 75 of 2009, MLM business schemes can use several contracts, namely murabaha, wakalah bi al-ujrah, ju'alah, ijarah and other contracts determined by DSN-MUI according to sharia principles, one of them is the Samsarah contract. However, the contract that is widely used in MLM business schemes is the ju'alah contract. Meanwhile, if you look at the MLM business scheme, which contains elements of intermediary services, services for selling products and recruiting new members which are part of the achievements that must be completed, then the appropriate contract is a hybrid contract between a samsarah contract and a ju'alah contract.